Treatment of postoperative accessory bile duct injury by fibrin glue and balloon tamponade: a case report - Bonati, Elena; Gnocchi, Alessandro; Cremaschi, Elena; Viani, Lorenzo; Dell'Abate, Paolo (Acta Biomedica Atenei Parmensis, 2019)
Laparoscopic cholecystectomy has become the gold standard for the treatment of symptomatic cholelithiasis. Iatrogenic bile duct injuries are still a diagnostic and therapeutic problem and their incidence increased with the introduction of laparoscopic technique. This case report documents a patient with a biliary fistula from an accessory bile duct - Lushka’s duct - after routine laparoscopic cholecystectomy, unresponsive to relaparoscopy, ERCP with papillosphincterotomy, biliary stent and nosobiliary tube placement and finally treated with injection of fibrin glue and balloon tamponade through the external drain. Iatrogenic bile duct injuries remain a challenging problem, in particular when they do not communicate with central biliary tree. The detection of this fistulas is more difficult and their management should be multidisciplinary. This case presentation is to emphasize importance of correct diagnostic evaluation and timely and adequate non-surgical methods of treatment of biliary fistulas. (www.actabiomedica.it)